Pengendalian Keselamatan dan Kesehatan Kerja Kegiatan Laboratorium Menggunakan Job Safety Analysis (Akuisisi Data Geolistrik) - Nunung Isnaini Dwi Ningsih (Integrated Lab Journal, 2022)
Research has been carried out on controlling occupational health safety in laboratory activities, namely the acquisition of geoelectrical data using the Job Safety Analysis (JSA) method. Primary data was obtained through direct observation in the field, while secondary data was obtained from documents related to the implementation of JSA. The purpose of this study is to determine the types of hazards that arise in geoelectric data acquisition activities. The results obtained will be the first step in preventing work accidents in these activities. Based on the research, it was found that the JSA method helps in identifying the hazards that arise in geoelectrical data acquisition activities and making controls to minimize each risk that may arise. In the acquisition of geoelectrical data, there are 3 (three) stages of work, namely personnel preparation, track preparation, and equipment installation. Through the JSA method, at each stage, the details of the work are made and then the identification of hazards, risks, and their control is carried out. At the three stages of work, all three can pose a hazard in terms of physics, chemistry, biology, ergonomics, and psychology. Those in charge of geoelectric data acquisition are supervisors and workers, Supervisors, in this case, are practicum lecturers or assistants or Educational Laboratory Institutions (PLP)/Labors, and workers, in this case, our students. To minimize all types of hazards, in the 3 (three) stages of the work, firstly for personnel preparation, it must be ensured that all personnel has attended K3 training on geoelectric data acquisition. All personnel participate in Safety Induction before carrying out the data acquisition process. At the stage of track preparation and equipment installation, it must be ensured that the equipment is ready for use in the field and that personal protective equipment is available in accordance with the OHS requirements for geoelectric data acquisition.